Identification of triterpene biosynthetic genes from Momordica charantia using RNA-seq analysis. Issue 2 (1st February 2019) - Takase, Shohei; Kera, Kota; Hirao, Yuya; Hosouchi, Tsutomu; Kotake, Yuki; Nagashima, Yoshiki; Mannen, Kazuto; Suzuki, Hideyuki; Kushiro, Tetsuo
ABSTRACT: Cucurbitaceae plants contain characteristic triterpenoids. Momordica charantia, known as a bitter melon, contains cucurbitacins and multiflorane type triterpenes, which confer bitter tasting and exhibit pharmacological activities. Their carbon skeletons are biosynthesized from 2, 3-oxidosqualene by responsible oxidosqualene cyclase (OSC). In order to identify OSCs in M. charantia, RNA-seq analysis was carried out from ten different tissues. The functional analysis of the resulting four OSC genes revealed that they were cucurbitadienol synthase (McCBS), isomultiflorenol synthase (McIMS), β-amyrin synthase (McBAS) and cycloartenol synthase (McCAS), respectively. Their distinct expression patterns based on RPKM values and quantitative RT-PCR suggested how the characteristic triterpenoids were biosynthesized in each tissue. Although cucurbitacins were finally accumulated in fruits, McCBS showed highest expression in leaves indicating that the early step of cucurbitacins biosynthesis takes place in leaves, but not in fruits. Abbreviations : OSC: oxidosqualene cyclase; RPKM: reads perkilobase of exon per million mapped reads Graphical abstract: : Four oxidosqualene cyclase genes were identified from M. charantia including cucurbitadienol synthase responsible for cucurbitacins biosynthesis.